Secreted Citrate Serves as Iron Carrier for the Marine Pathogen Photobacterium damselae subsp damselae - Balado, Miguel; Puentes, Beatriz; Couceiro, Lucía; Fuentes-Monteverde, Juan C.; Rodríguez, Jaime; Osorio, Carlos R.; Jiménez, Carlos; Lemos, Manuel L. (Frontiers in Cellular and Infection Microbiology, 2017)
Photobacterium damselae subsp damselae (Pdd) is a Vibrionaceae that has a wide pathogenic potential against many marine animals and also against humans. Some strains of this bacterium acquire iron through the siderophore vibrioferrin. However, there are virulent strains that do not produce vibrioferrin, but they still give a strong positive reaction in the CAS test for siderophore production. In an in silico search on the genome sequences of this type of strains we could not find any ORF which could be related to a siderophore system. To identify genes that could encode a siderophore-mediated iron acquisition system we used a mini-Tn10 transposon random mutagenesis approach. From more than 1,400 mutants examined, we could isolate a mutant (BP53) that showed a strong CAS reaction independently of the iron levels of the medium. In this mutant the transposon was inserted into the idh gene, which encodes an isocitrate dehydrogenase that participates in the tricarboxylic acid cycle. The mutant did not show any growth impairment in rich or minimal media, but it accumulated a noticeable amount of citrate (around 7 mM) in the culture medium, irrespective of the iron levels. The parental strain accumulated citrate, but in an iron-regulated fashion, being citrate levels 5-6 times higher under iron restricted conditions. In addition, a null mutant deficient in citrate synthase showed an impairment for growth at high concentrations of iron chelators, and showed almost no reaction in the CAS test. Chemical analysis by liquid chromatography of the iron-restricted culture supernatants resulted in a CAS-positive fraction with biological activity as siderophore. HPLC purification of that fraction yielded a pure compound which was identified as citrate from its MS and NMR spectral data. Although the production of another citrate-based compound with siderophore activity cannot be ruled out, our results suggest that Pdd secretes endogenous citrate and use it for iron scavenging from the cell environment.